X-ray photoelectron spectra and features of the electronic-energy structure of oxygen-stabilized phases of Zr4Fe2O and Zr4Ni2O - Lavrent’yev, A.A.; Shkumat, P.N.; Kopylova, E. I.; Gabrel’yan, B.V.; Sinel’nichenko, A.K.; Zavalii, I.Yu.; Khizhun, O.Yu. (Reports of the National Academy of Sciences of Ukraine, 2014)
X-ray photoelectron (XP) spectra have been derived, and the ab initio calculations of the electronic structure have been made for Zr4Fe2O and Zr4Ni2O oxides, prospective hydrogen absorbing materials. The XP valence-band spectrum of Zr4Fe2Ox has been compared on a single energy scale with the curve of the total density of states of the oxide. A good agreement of the theoretical and experimental results regarding the electronic structure of Zr4Fe2O has been achieved. The theoretical data reveal the similarity of the electronic structure of Zr4Fe2O and Zr4Ni2O oxides and indicate that their valence bands are dominated by contributions of Fe(Ni)3d states. These states contribute predominantly in the upper part of the valence band.